2021
DOI: 10.1017/aer.2021.23
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional guidance and control for ground moving target tracking by a quadrotor

Abstract: This paper develops a three-dimensional guidance and control algorithm to ensure that a manoeuverable target is preserved by a quadrotor in a long-term tracking scenario. The proposed guidance approach determines the desired altitude of the quadrotor to adjust the field of view (FOV) to the union of two desired trusted and critical regions. The dimensions of the desired trusted region depend on the controller performance that is evaluated by the distance of the target from the center of the FOV. The critical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Monocular imaging systems are not capable to consider the object depth, even though this is compensated with methods like the one presented in [30], where a real-time object localization and tracking strategy from monocular image sequences is proposed, using a dynamic Kalman model to integrate object detection and tracking. Improving the tracking performance as well as avoiding manual initialization for tracking is proposed in [31]. On the other hand, [32] report a method that merges optical flow and background subtraction to detect and track multiple moving targets from a UAV; moreover, the authors assume that the background and the UAV have diverse motion patterns, and employ a Kalman filter to reduce the miss-detection and false alarms.…”
Section: Tracking Of Moving Objectsmentioning
confidence: 99%
“…Monocular imaging systems are not capable to consider the object depth, even though this is compensated with methods like the one presented in [30], where a real-time object localization and tracking strategy from monocular image sequences is proposed, using a dynamic Kalman model to integrate object detection and tracking. Improving the tracking performance as well as avoiding manual initialization for tracking is proposed in [31]. On the other hand, [32] report a method that merges optical flow and background subtraction to detect and track multiple moving targets from a UAV; moreover, the authors assume that the background and the UAV have diverse motion patterns, and employ a Kalman filter to reduce the miss-detection and false alarms.…”
Section: Tracking Of Moving Objectsmentioning
confidence: 99%
“…After a quadrotor is designed, c.f. (Domingues, 2009;Sepehri Movafegh et al, 2021), several parameters need to be identified to obtain approximates of their actual values. This identification is done usually off-line before even the quadrotor is deployed for the first time (Bresciani, 2008;Krznar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%